Biópsia pulmonar incisional por toracoscopia paraxifóide transdiafragmática com dois portais em cães - Basso, Paula Cristina (2009)
There are lot of respiratory diseases in small animals, as well as the possibilities of diagnoses, as laboratory and radiographic exams, bronchoalveolar lavage and biopsies, but all of them in association with a detailed physical examination. This research aimed at assessing of the results of transdiaphragmatic paraxiphoid thoracoscopies in pulmonary biopsies of thirteen clinically healthy dogs. Under general anesthesia, each dog was insufflated with 30ml kg-1 of air in each hemithorax; two trocars were placed between the xiphoid appendix and the costal arch through the diaphragm. An endoscope was introduced by the first portal; while the second portal was used to allow access to the nippers in the biopsy forceps. Then, these nippers were removed and replaced by chest tube drainage. During the procedures, respiratory frequency, heart rate, oxygen saturation, arterial pressure and central venous pressure (CVP), hemogasometric parameters were checked. Within 48 hours after the surgery, drains were or drain was removed, with minimal production of air and/or liquid. In conclusion, this is a fast and safe technique, which is free of trans and post surgical complications, thus allowing the collection of sufficient material for pulmonary histological evaluation.